CAPITALIZATION OF ASSETS AS THE â€œMYSTERYâ€ BEHIND CAPITAL - Lilis Mulyani (LIPI Press, 2006)
Title of Book : The Mystery of Capital Author : Hernando de Soto Year Published : 2000 Number of pages : 276 pages